Marking Time in Memorials and Museums of Terror: Temporality and Cultural Trauma. (March 2020) - Simko, Christina
The theory of cultural trauma focuses on the relationship between shared suffering and collective identity: Events become traumatic when they threaten a group's foundational self-understanding. As it stands, the theory has illuminated profound parallels in societal suffering across space and time. Yet focusing on identity alone cannot explain the considerable differences that scholars document in the outcomes of the trauma process. Namely, while some traumas become the basis for moral universalism, generating a capacity to forge connections between an in-group's suffering and that of out-groups, others have the opposite effect, leading to particularism and closure. Returning to the interdisciplinary literature on trauma, I argue for incorporating temporality as a twin pillar of the trauma process, distinguishing between acting out (reexperiencing a past event as the present) and working through (situating a painful event within historical context). A comparison of three U.S. sites of memory dealing with terrorism illustrates the distinction.